1995
DOI: 10.1159/000227478
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Biochemical Long–Term Toxicity after Postoperative Cisplatin–Based Chemotherapy in Patients with Low-Stage Testicular Cancer

Abstract: In this case-control study the long-term chemotherapy-related morbidity was assessed in testicular cancer patients (≥5 years after treatment). The case group consisted of 47 patients with nonseminomatous testicular cancer who had undergone retroperitoneal surgery and 3-4 cycles of conventional-dose cisplatin-based chemotherapy (accumulated cisplatin dose: 300-400 mg/m2), also containing vinblastine and bleomycin. The results of the clinical and biochemical investigations and the patients’ responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…A Leydig cell impairment, with subnormal/normal s-testosterone values and/or increased luteinizing hormone (LH), was found in patients who had undergone chemotherapy (5)(6)(7)(8). However, in other studies, no difference in testosterone or LH after chemotherapy was found (9,10).…”
Section: Introductionmentioning
confidence: 97%
“…A Leydig cell impairment, with subnormal/normal s-testosterone values and/or increased luteinizing hormone (LH), was found in patients who had undergone chemotherapy (5)(6)(7)(8). However, in other studies, no difference in testosterone or LH after chemotherapy was found (9,10).…”
Section: Introductionmentioning
confidence: 97%
“…Although a great number of studies have been published about the long-term adverse effects of chemotherapy such as nephrotoxicity [7], renal magnesium wasting [8], Raynaud's phenomenon [9], neurotoxicity [10], gonadal dysfunction [11], and unfavorable cardiovascular risk factors including hypertension, overweight, and hypercholesterolemia [12,13], some of the findings are contradictory. Besides, the long-term quality of life of these patients following chemotherapy has gained importance, and studies questioning this quality which include the physical, psychological, and social functions of the patient have been carried out [14].…”
Section: Introductionmentioning
confidence: 99%
“…There are several limitations associated with the use of cisplatin (Kim and Glisson, 2003;Milas et al, 2003). There are serious side effects, notably renal toxicity, emesis, neurotoxicity, bone marrow suppression, and hearing loss (Tsutsumi et al, 1991;Fossa et al, 1995). Another major impediment to the clinical success of cisplatin is cellular resistance to the drug, through either intrinsic or acquired resistance .…”
Section: Introductionmentioning
confidence: 99%